Ibn Taymiyya's theodicy of perpetual optimism - Hoover, Jon. (Islamic Philosophy, Theology and Science. Texts and Studies, 2007)
The Muslim jurist Ibn Taymiyya (d. 1328) is famous for polemic against Islamic philosophy, theology and rationalizing mysticism, but his positive theological contribution has not been well understood. This comprehensive study of Ibn Taymiyya's theodicy helps to rectify this lack. Exposition and analysis of Ibn Taymiyya's writings on God's justice and wise purpose, divine determination and human agency, the problem of evil, and juristic method in theological doctrine show that he articulates a theodicy of optimism in which God in His essence perpetually wills the best possible world from eternity. This sets Ibn Taymiyya's theodicy apart from Ashʿarī divine voluntarism, the free-will theodicy of the Muʿtazilīs, and the essentially timeless God of other optimists like Ibn Sīnā and Ibn ʿArabī.